The role of ozone treatment as integrative medicine. An evidence and gap map - Serra, Maria Emilia Gadelha; Baeza-Noci, José; Mendes Abdala, Carmen Verônica; Luvisotto, Marilia Moura; Bertol, Charise Dallazem; Anzolin, Ana Paula (Frontiers in Public Health, 2023)
Introduction: The Brazil has one of the largest public health systems in the world and in the 1980s, Traditional, Complementary and Integrative Medicine were introduced. In 2018, the treatment with ozone became a complementary integrative practice showing several benefits. However, its effectiveness needs to be researched. The objective of this evidence gap map is to describe contributions of Integrative Medicines-Ozone treatment in different clinical conditions, to promote evidence-based practice. Methods: We applied the methodology developed by Latin American and Caribbean Center on Health Sciences Information based on the 3iE evidence gap map. The EMBASE, PubMed and Virtual Health Library databases, using the MeSH and DeCS terms for the treatment with Ozone were used. Results: 26 systematic reviews were characterized, distributed in a matrix containing 6 interventions (parenteral oxygen/ozone gas mixture; parenteral ozonated water; systemic routes; topical application ozonated water; topical oxygen/ozone gas mixture; and topical ozonated oil) and 55 outcomes (cancer, infection, inflammation, pain, quality of life, wound healing and adverse effects). 334 associations between intervention and outcome were observed, emphasizing the parenteral oxygen/ozone gas mixture intervention (192 associations, 57%). Conclusions: The evidence gap map presents an overview of contributions of Ozone treatment in controlling pain, infections, inflammation and wound healing, as well as increasing the quality of life, and it is directed to researchers and health professionals specialized in Ozone treatment. No serious adverse effects were related. Therefore, this treatment may be even more widely known as an integrative treatment, considering its low cost, efficiency and safety. Future studies should adopt economic impact assessments and the organization of health services.